Resource Management & Healthy Purchasing Behaviors Show Direct Effects on Diet Change in Pathway Analysis Exploring Mechanisms of Action for a Produce Prescription Program. (7th June 2021) - Cook, Miranda; Obrutu, Okezi; Reasoner, Tammy; Bursuc, Courtney; Taylor, Kathy; Moore, Sarah; Schmidt, Stacie; Girard, Amy Webb
Abstract: Objectives: Investigate the mechanisms of action in a produce prescription program through pathway analysis. Methods: The Georgia Food for Health program is a produce prescription program that provides cooking classes, nutrition education, and vouchers redeemable for produce over a six-month intervention period. Program data collected between 2018 and 2019 were used to fit a pathway model estimating the relationships in the program. Measures included the number of program visits attended, per-person total produce voucher redemption (in US dollars), change in food security, diet score (based on a modified food frequency questionnaire), purchase score (a measure of healthy purchasing behaviors), resource score (a measure of resource management behaviors), as well as blood pressure, waist circumference, and BMI. The model controlled for sex and age of participant as well as site and year of program participation. Model fit was interpreted based on the following indices: Root Mean Squared Error of Approximation (RMSEA), Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), and Standardized Root Mean Squared Residual (SRMR). The lavaan package version 0.6–3 in R software was used for the pathway analysis component. Results: Neither number of visits attended nor per-person total redemption had direct effects on change in resource score or change in purchase score from baseline to endline of the program. Change in resource score had a moderate direct effect on change in diet score (β = 0.185, P  < 0.05). Change in purchase score also had a moderate direct effect on change in diet score (β = 0.149, P  < 0.05). No factors had significant effects on change in food security. Diet score did not have significant effects on change in clinical outcome measures. Model fit was good with RMSEA <0.001, CFI is >0.95, TLI >0.95, and SRMR <0.08. Conclusions: Produce prescription programs show promise of improving diet scores through improving healthy purchasing and resource management behaviors. Additional research is needed to determine factors that influence changes in these behaviors and how to maximize their effects for similar programs. Funding Sources: Supported partially by the National Center for Advancing Translational Sciences of the National Institutes of Health under Award Number UL1TR002378. Additional funding provided by Open Hand Atlanta.